Pride and shame in the city: young people's experiences of rural-urban migration in India - Datta, Amrita (Children's geographies, 2018)
This article explores the complex emotional experiences of young male rural migrants in the city of Delhi, India. Based on multi-sited fieldwork, and drawing on a long-term study in Bihar, India, this paper contributes to emerging scholarship on the emotional geographies of migration that prioritise young people's perspectives. I show that while young migrants are active agents in their own migration, they are also subject to specific vulnerabilities and exploitation. At the same time, they undertake challenging emotional labour in the city to create particular working identities that are both a source of pride and shame. I argue that an insertion of emotions in the analysis of migration helps disentangling this dissonance between migrants' economic success and social rejection in the city. The article makes a case for the incorporation of emotions for a more comprehensive and nuanced analysis of young people's migration in academic and policy discourses.